Effects of LY274614, a competitive NMDA receptor antagonist, on the micturition reflex in the urethane-anaesthetized rat. - Yoshiyama, M. (Nature Publishing Group, 1993)
1. The effects of 3 competitive N-methyl-D-aspartate (NMDA) receptor antagonists, LY274614, LY233536 and LY235723, on the micturition reflex and external urethral sphincter EMG activity, were examined either under isovolumetric conditions or during continuous filling cystometry in urethane-anaesthetized (1.2 g kg-1, s.c.) rats. 2. Intravenous administration of LY274614 (3-30 mg kg-1) inhibited in a dose-dependent fashion both bladder and sphincter activity in the intact rats. In addition, the volume threshold for inducing micturition was increased and voided volume was decreased. 3. Intrathecal administration of LY274614 (0.06-30 micrograms) similarly inhibited bladder and sphincter activity during cystometry in intact rats. 4. In chronic spinal cord (T6-T8) transected rats LY274614 (0.1-30 mg kg-1, i.v.) did not alter bladder activity under isovolumetric conditions but decreased the amplitude of micturition contractions and sphincter EMG activity during cystometry at a dose of 10-30 mg kg-1. 5. The inhibitory effects of i.v. administration of LY274614, on bladder and sphincter activity induced by infusion of chemical irritant (0.1% acetic acid) or saline, were similar; except that a slightly larger dose was needed to inhibit sphincter activity during acetic acid infusion. 6. Peak amplitude of micturition contractions recovered to 50% of control 3 h following i.v. (30 mg kg-1) or i.t. (6 micrograms) administration of LY274614. 7. Two other chemically related NMDA antagonists, LY233536 and LY235723 produced similar but less potent effects than LY274614 when given i.v. 8. These data indicate that glutamatergic transmitter mechanisms at the level of the spinal cord are important in modulating bladder activity in the intact animal, but that these mechanisms do not contribute to bladder reflexes in the chronic spinal rat. These mechanisms may, however, contribute to sphincter activity in both intact or chronic spinal rats.